A tarifa horária para os consumidores residenciais sob o foco das redes elétricas inteligentes - REI - Figueiró, Iuri Castro (2013)
This Master s dissertation presents the development of a methodology to evaluate and estimate the behavior of the residential consumer facing the application of the white hourly tariff. In the context of the Smart Grids, this rate is applied aiming to encourage the consumers to shift their consumption to times of lower loading of system, looking for a better utilization of the infrastructure of the electric system. Considering this, the proposed methodology considers the analysis about the habits of use of electric shower, which is the household equipment that presents the greatest contribution on the final consumption and on the peak of the load curve of residential consumers. In this way the analysis considers data from the Brazilian Center of Information in Energy Efficiency - PROCEL INFO, which includes information about habits of use of household. This database, combined with the application of the Monte Carlo method, provide an overview of the possible effects of the application of the hourly rate to the consumers and to the electrical system, as well as, a guideline of actions that can be taken for a better adaptation of the consumers, considering this new trend.